Field-based upper-body motor variability as determinant of stroke performance in the main tennis strokes - Ruiz-Malagón, E. J.; Vanrenterghem, J.; Ritacco-Real, M.; González-Fernández, F. T.; Soto-Hermoso, V. M.; Delgado-García, G. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
Performance in tennis relies heavily on the skilful repetition of several types of tennis strokes, yet the role of motor variability has still received little scientific attention - especially at the within subject level. The present study aims to evaluate the role of motor variability depending on the strokes/body segment and the level of expertise. Thirty-five players performed a field test (including first and second serves, forehand and backhand strokes) with four synchronized gyroscopes placed on the trunk, head, upper arm and forearm. Variability was measured based on the coefficient of variation (CV) of the angular velocity peaks per stroke in each body segment. MANOVA revealed greater motor variability in the forehand and backhand than in the serve (p < 0.001), with head and forearm segments showing the highest variability (CV > 15% in some cases). This result also translated to differences in variability between levels of expertise, with variability being greater among lower level players (p < 0.02 in all strokes, with Cohen d > 1 in some cases). Summarized, groundstrokes could imply more compensatory kinematic movements to keep the result of the action stable. Motor variability must be considered to evaluate performance, as a reduced motor variability was found in players with higher level of expertise. The compensatory action of the body segments (especially in groundstrokes and in the forearm and head, where the coefficients of variation were high) should be studied in depth because it can help design motor tasks, making them more specific.